The Man Who Wrote Pancho Villa : Martin Luis Guzman and the Politics of Life Writing - Cifuentes-Goodbody, Nicholas (Book collections on Project MUSE., 2015)
"The Man Who Wrote Pancho Villa explores the way in which one author tried to shape and control his literary legacy through biographical and autobiographical writing"--Provided by publisher